The importance of folic acid for the prevention of myelomeningocele. An integrative literature review (Research, Society and Development, 2022)
Introduction: Meningomyelocele is one of the most common and worrying spina bifida malformations during the fetal formation process. Therefore, it is necessary to think about measures that aim to minimize its prevalence, as well as to alleviate the possible associated sequelae during the neonatal process. Objective: To determine the role of the use of folic acid as a food supplement during pregnancy in order to prevent or alleviate the manifestation of myelomeningocele. Methodology: An integrative literature review was carried out in the electronic search engines Pubmed, Cochrane Library, Embase, Scopus and Web of Science using the search strategy based on the MeSH terms “(Meningomyelocele) AND (Folic Acid) AND (Dietary Supplements)”. Results and Discussion: A total of 47 articles were retrieved and of these, 34 were selected based on the inclusion and exclusion criteria. The articles listed folic acid as one of the main alternatives for preventing the manifestation of meningomyelocele, having an even more important context for countries with high social inequality. Its supplementation can be given through the addition of flours that are a low-cost food base for government distribution. In addition, the need for information and nutritional monitoring in a multidisciplinary context throughout the prenatal period was highlighted, in order to guarantee information to families. Conclusion: Folic acid supplementation is an effective and low-cost measure to prevent meningomyelocele, however, a multidisciplinary follow-up throughout the prenatal period is extremely important to really demonstrate good epidemiological results.Keywords: Meningomyelocele; Folic Acid; Dietary Supplements; Review.